1990
DOI: 10.2307/30144265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Infection of Central Venous Catheters Used for Total Parenteral Nutrition

Abstract: To identify predictors of infection in catheters used for total parenteral nutrition (TPN), clinical and microbiological data were prospectively collected on 169 catheter systems (88 patients). Based on semiquantitative catheter cultures, infection was associated with a positive insertion site skin culture taken close to the time of catheter removal (relative risk [RR] = 4.50), especially one yielding greater than or equal to 50 colonies of an organism other than coagulase-negative staphylococci. Infection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 25 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…Few studies have investigated skin insertion sites cultures in ICU patients (82). In patients with long-term nutrition catheters, negative site cultures had a negative predictive value for line infection of 98% (83), whereas positive culture, particularly of organisms other than coagulase-negative staphylococci, is predictive of CVC infection (79). In patients with nontunneled CVCs, the presence of Ͼ50 cfu of organisms by quantitative skin site cultures at the time of removal for suspected infection had a sensitivity of 75%, a positive predictive value of 100% and a negative predictive value of 92% in detecting CVC infection (84).…”
Section: Grade Dmentioning
confidence: 95%
See 2 more Smart Citations
“…Few studies have investigated skin insertion sites cultures in ICU patients (82). In patients with long-term nutrition catheters, negative site cultures had a negative predictive value for line infection of 98% (83), whereas positive culture, particularly of organisms other than coagulase-negative staphylococci, is predictive of CVC infection (79). In patients with nontunneled CVCs, the presence of Ͼ50 cfu of organisms by quantitative skin site cultures at the time of removal for suspected infection had a sensitivity of 75%, a positive predictive value of 100% and a negative predictive value of 92% in detecting CVC infection (84).…”
Section: Grade Dmentioning
confidence: 95%
“…In patients with nontunneled CVCs, the presence of Ͼ50 cfu of organisms by quantitative skin site cultures at the time of removal for suspected infection had a sensitivity of 75%, a positive predictive value of 100% and a negative predictive value of 92% in detecting CVC infection (84). In another study, a site culture yielding Ͼ50 cfu coagulase-negative staphylococci was associated with a 4.4 times greater risk of catheter colonization (79). However, in one study, the positive predictive value of nonquantitative insertion site culture was only 29% (85).…”
Section: Grade Dmentioning
confidence: 96%
See 1 more Smart Citation
“…In a clinical study conducted by Collignon et al 85% of catheters colonized by >100 CFU (SQM) were associated with CRB 28 . Armstrong et al found a correlation for SQM >15 CFU on catheter tips and a colonization of the skin insertion site (>50 CFU) with CRI of catheters used for total parenteral nutrition 29 . Comparative quantitative blood cultures via CVC and peripheral blood with a 5-fold difference was significant for CRS 30 which has been widely accepted.…”
Section: Diagnosis Of Catheter Related Infectionmentioning
confidence: 99%
“…However, most studies (Brendel, 1983;Messner, 1985) suggest that the distal 5 cm of the catheter be clipped off with sterile scissors and sent to the laboratory in a sterile container (not in culture medium) for culture. In most studies (Sitzmann et al, 1985;Maki & Ringer, 1987;Armstrong et al, 1990), it is generally agreed that there is a significant association between a positive skin culture and catheter infection. It was also generally agreed that when the patient showed signs of infection, blood cultures were done from the catheter and/or from a peripheral vein, the catheter was removed and the patient given antibiotics.…”
Section: Protective Barrier Against Mierobesmentioning
confidence: 99%